Selection index for meat and milk traits of buffaloes in Colombia (2016)
ABSTRACT: Genetic parameters and breeding values from unitrait, multitrait, and reduced principal component models for weaning weight, yearling weight, weight at 18 months, weight at two years, age at first calving, milk yield, and maternal genetic effects for weaning weight and yearling weight were estimated for dual purpose buffaloes in Colombia. With those values we constructed selection indices (SI) and estimated genetic progress obtained through mating-modeling under various selection criteria and weighted values for each trait. Comparison of SI was performed using duality diagrams in principal components of breeding values obtained by pseudo-simulation of mating with animals selected with the constructed SIs. The index constructed with the first principal component of the reduced range model led to improved meat, milk yield, and age at first calving.